2007
DOI: 10.1038/sj.npp.1301550
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Mechanisms of Fear Extinction and Depression-Like Behavior

Abstract: Human anxiety is frequently accompanied by depression, and when they co-occur both conditions exhibit greater severity and resistance to treatment. Little is known, however, about the molecular processes linking these emotional and mood disorders. Based on previously reported phosphorylation patterns of extracellular signal-regulated kinase (ERK) in the brain, we hypothesized that ERK's upstream activators intertwine fear and mood regulation through their hippocampal actions. We tested this hypothesis by study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 75 publications
3
65
0
Order By: Relevance
“…Thus, the deficiency in long-term memory in Erk2 CKO mice was caused by the loss of ERK2 per se, rather than by a secondary upregulation of ERK1 activity. It was also reported that in mice lacking ERK1, ERK2 did not only compensate for the lack of ERK1, but also exhibited stronger biological activity in some regions (Mazzucchelli et al, 2002;Tronson et al, 2008). Erk1 KO mice exhibited dramatic enhancement of striatum-dependent long-term memory likely due to enhanced activation of ERK2 (Mazzucchelli et al, 2002).…”
Section: Central Contribution Of Erk2 To Brain Functionsmentioning
confidence: 99%
“…Thus, the deficiency in long-term memory in Erk2 CKO mice was caused by the loss of ERK2 per se, rather than by a secondary upregulation of ERK1 activity. It was also reported that in mice lacking ERK1, ERK2 did not only compensate for the lack of ERK1, but also exhibited stronger biological activity in some regions (Mazzucchelli et al, 2002;Tronson et al, 2008). Erk1 KO mice exhibited dramatic enhancement of striatum-dependent long-term memory likely due to enhanced activation of ERK2 (Mazzucchelli et al, 2002).…”
Section: Central Contribution Of Erk2 To Brain Functionsmentioning
confidence: 99%
“…it is well-established that stress exposure activates the erK1/2 signaling pathway (11,12), and it has been speculated that the erK signaling pathway in the lateral amygdala is involved in anxiety (13,14). Generally, activation of erK1/2 promotes cell survival; however, under certain conditions, erK1/2 exhibits pro-apoptotic functions (15).…”
Section: Introductionmentioning
confidence: 99%
“…At a molecular level, the extracellular signal-regulated kinase (Erk) has recently been identified as an important mediator of fear extinction (Szapiro et al 2003;Chen et al 2005;Tronson et al 2008). Erk shows rapid and sustained phosphorylation shortly preceding and during fear extinction, which subsides after fear has stably extinguished (Fischer et al 2007;Ryu et al 2008).…”
mentioning
confidence: 99%